'Stone is stone': engagement and detachment in the craft of conservation masonry. (June 2014) - Yarrow, Thomas; Jones, Siân
<x xml:space="preserve">Abstract</x> Since the mid‐nineteenth century, craft has been characterized by relations of engagement, resonating with broader romantic discourses that idealize craftsmen in explicit contrast to forms of alienation linked to capitalist production. In recent work on craft, the analytic lens of engagement usefully highlights the dynamic interplay of human and non‐human agencies. Our own account builds on these ideas but suggests that the conceptual privileging of engagement creates interpretative problems, precluding ethnographic attention to the role of detachment in craft. Focusing on the skilled practices of conservation stonemasons, we describe the specific constellations of ideology and practice involved in cutting and fixing stone. Through elucidating masons' own understandings of their work, we highlight their commitment to the 'disciplined' embodiment of tradition as a means of separating personal subjectivity from the stones they carve. Our analysis of the skilled practices required to work stone questions the primacy of engagement, suggesting instead that detachment and engagement are mutually implicated relational forms. This finding sheds new light on craft practice and offers a position from which to reconsider broader anthropological commitments to concepts of engagement.